2017
DOI: 10.1080/1331677x.2017.1355252
|View full text |Cite
|
Sign up to set email alerts
|

Why governments may opt for financial repression policies: selective credits and endogenous growth

Abstract: Financial repression policies (lowering real interest rates, selective credits and other restrictions on financial markets, products and institutions) have been widely discussed in the economic literature during the last four decades. A key question is 'why governments would opt for financial repression policies in the first place'? As an answer, governments' desire to obtain rents from the financial system or to manage public debt servicing have been suggested as the typical underlying incentives. It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Bruce and Turnovsky (2013a) have attributed the growth in the economy to demographic factors like fertility, life expectancy, age among others (see Bruce & Turnovsky, 2013b; Yew & Zhang, 2013; Mierau & Turnovsky, 2014; Bloom, Canning, & Sevilla, 2004; Well, 2007). Another strand of studies has created a link between growth and macroeconomic variables, and has also identified different directions of causality between both (Alfaro, Chanda, Kalemli‐Ozcan, & Sayek, 2004; Ivanović & Stanišić, 2017; Prašnikar, Redek, & Drenkovska, 2017; Yülek, 2017). Recently, institutional qualities have also been assigned a chief role in determining economic growth (Acemoglu, Johnson, & Robinson, 2005; Barro, 2003; Bildirici, 2008; Butkiewicz & Yanikkaya, 2006; Chong & Calderon, 2000; Fraj, Hamdaoui, & Maktouf, 2018; Gwartney, Holcombe, & Lawson, 2004; Henderson, Papageorgiou, & Parmeter, 2011; Ji, Magnus, & Wang, 2014; Klein, 2005; Law, Azman‐Saini, & Ibrahim, 2013; Sobel, 2008; Valeriani & Peluso, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bruce and Turnovsky (2013a) have attributed the growth in the economy to demographic factors like fertility, life expectancy, age among others (see Bruce & Turnovsky, 2013b; Yew & Zhang, 2013; Mierau & Turnovsky, 2014; Bloom, Canning, & Sevilla, 2004; Well, 2007). Another strand of studies has created a link between growth and macroeconomic variables, and has also identified different directions of causality between both (Alfaro, Chanda, Kalemli‐Ozcan, & Sayek, 2004; Ivanović & Stanišić, 2017; Prašnikar, Redek, & Drenkovska, 2017; Yülek, 2017). Recently, institutional qualities have also been assigned a chief role in determining economic growth (Acemoglu, Johnson, & Robinson, 2005; Barro, 2003; Bildirici, 2008; Butkiewicz & Yanikkaya, 2006; Chong & Calderon, 2000; Fraj, Hamdaoui, & Maktouf, 2018; Gwartney, Holcombe, & Lawson, 2004; Henderson, Papageorgiou, & Parmeter, 2011; Ji, Magnus, & Wang, 2014; Klein, 2005; Law, Azman‐Saini, & Ibrahim, 2013; Sobel, 2008; Valeriani & Peluso, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…If household and enterprise lending have an independent impact on growth, it might shape our understanding of why the effect of financial development on economic growth varies across countries, as well as provide some important insights regarding the channels through which financial intermediaries stimulate GDP growth (see Beck et al, 2008). Financial repression policies have strong impact on the finance-growth link (Yülek, 2017) as well as monetary freedom (Ivanović & Stanišić, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Yülek contended that industrial policies could be likened to a credit endorsement bestowed by the government upon enterprises, offering external investors a clear economic trajectory. Such assurances significantly diminished investor risk apprehensions, thereby drawing increased capital participation 33 . Barbieri et al (2021) argued that, under the guidance and encouragement of industrial policies, corporate actions became more aligned with national strategic objectives 34 .…”
Section: The Direct Impact Of Industrial Policy On Cross-border Merge...mentioning
confidence: 99%